Penerapan cerpen dan media susun kata sebagai alat bantu pembelajaran bahasa indonesia untuk meningkatkan kemampuan membaca pada siswa sekolah dasar di salatiga - Zila Mu’adila , Ina Ardiya Aprevianti, (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2025)
This study aims to deeply analyze the effectiveness of using short stories and word-building media as teaching aids to improve the reading skills of elementary school students, particularly in first-grade classes at several elementary schools in Salatiga. The method employed in this research involved direct interviews with students as an instrument to evaluate the impact of implementing these two learning media. Based on the interview results, the majority of students expressed that they felt more enthusiastic about learning Indonesian when using short stories and word-building media, as the approach applied was more interactive, varied, and enjoyable. Additionally, the students acknowledged that their reading and writing skills had significantly improved due to the use of these teaching methods. Thus, it can be concluded that short stories and word-building media have proven to be effective learning tools in enhancing the reading skills of elementary school students, contributing positively to the overall development of their language abilities.